Transcallosal Inhibition during Motor Imagery: Analysis of a Neural Mass Model - Mangia, Anna L.; Ursino, Mauro; Lannocca, Maurizio; Cappello, Angelo (Frontiers in Computational Neuroscience, 2017)
The EEG rhythmic activities of the somato-sensory cortex reveal event-related desynchronization (ERD) or event-related synchronization (ERS) in beta band (14-30 Hz) as subjects perform certain tasks or react to specific stimuli. Data reported for imagination of movement support the hypothesis that activation of one sensorimotor area can be accompanied by deactivation of the other. In order to improve our understanding of beta ERD/ERS generation, two neural mass models of a cortical column taken from Wendling et al (2002) were interconnected to simulate the transmission of information from one cortex to the other. The results show that the excitation of one cortex leads to inhibition of the other and vice versa, enforcing the Theory of Inhibition. This behaviour strongly depends on the initial working point of the neural populations (between the linear and the upper saturation region of a sigmoidal function) and on how the cortical activation or deactivation can move the working point in the upper saturation region (ERD) or in the linear region (ERS) respectively.